Pengaruh Geometrik Jalan Terhadap Tingkat Kecelakaan Lalu Lintas - Selen , Karolus; Pandulu , Galih Damar; Rahma , Pamela Dinar (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2023)
The topographical conditions that are quite dangerous on the Bromo Highway section cause many sharp turns, uphill roads and downhill which are quite dangerous to pass. The lack of adequate road complementary facilities will have an impact on the risk of traffic accidents. The occurrence of traffic accidents in 2016-2021 on the Raya Bromo road section is one of the accidents that caused a lot of property losses and casualties. This study aims to determine how much influence road geometrics have on the level of traffic accidents, so that solutions are obtained to reduce the risk of accidents. Analysis of road geometrics using the 1997 TPGJAK standard, MKJI 1997 and Polynomial Regression Analysis. The results of the analysis using Polynomial Regression of the Horizontal and Vertical Alignment relationship to the EAN value, Side Free Area R² 57%, Finger Finger 27%, Degree of Curvature, 26%, Superelevation 36%, and slope R² 50.04%. Based on the results of the analysis, it is necessary to improve the Horizontal Alignment in existing conditions, namely PI1 (SS), PI2 (SS), PI3 (SS), PI4 (SS), PI5 (SS), PI6 (SS), PI7 (SS), PI8 (SCS), PI9 (SS), PI10 (SS), while for Vertical Alignment by changing the slope at points PIC-PI3 (12%), PII-PI9 (11%), and adding adequate road complementary facilities in accordance with technical specifications.